2023
DOI: 10.21203/rs.3.rs-3439762/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inequalities in the prevalence of Caesarean section and associated factors in rural and urban Nigeria: insights from the 2018 Nigeria Demographic and Health Survey

Emmanuel O Adewuyi,
Wole Akosile,
Victory Olutuase
et al.

Abstract: Introduction When medically indicated, caesarean section (CS) can be a lifesaving intervention for mothers and their newborns. This study assesses the within-population CS prevalence and associated factors with an emphasis on inequalities between rural and urban areas in Nigeria. Methods We disaggregated the 2018 Nigeria Demographic Health Survey and performed analysis separately for the overall, rural, and urban residences in Nigeria. Data were summarised using frequency tabulations, and factors associated wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…While nationally, the association was only marginally significant, the influence of Internet exposure suggests a potential avenue for disseminating information about ANC services, towards fostering awareness and encouraging health-seeking behaviours. This finding resonates with recent research highlighting the role of internet access in Caesarean Section utilisation, particularly in urban Nigeria [ 44 ]. The United Nations recognises unrestricted internet access as a fundamental human right [ 53 , 54 ], underlining its importance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While nationally, the association was only marginally significant, the influence of Internet exposure suggests a potential avenue for disseminating information about ANC services, towards fostering awareness and encouraging health-seeking behaviours. This finding resonates with recent research highlighting the role of internet access in Caesarean Section utilisation, particularly in urban Nigeria [ 44 ]. The United Nations recognises unrestricted internet access as a fundamental human right [ 53 , 54 ], underlining its importance.…”
Section: Discussionsupporting
confidence: 89%
“…Regional differences were also pronounced, with southern regions generally exhibiting higher ANC utilisation than northern regions, particularly the North-East. Many studies have reported regional differences or gaps between southern and northern Nigeria [ 5 , 16 , 44 , 45 ]. These disparities may mirror the intersectionality of geographic location with other social determinants, such as security challenges, poor educational development, and low accessibility to healthcare services.…”
Section: Discussionmentioning
confidence: 99%